2021
DOI: 10.3389/fpsyg.2021.672610
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement in Mathematics Flipped Classrooms: Implications of Journal Publications From 2011 to 2020

Abstract: Mathematics is one of the core STEM (science, technology, engineering, and mathematics) subject disciplines. Engaging students in learning mathematics helps retain students in STEM fields and thus contributes to the sustainable development of society. To increase student engagement, some mathematics instructors have redesigned their courses using the flipped classroom approach. In this review, we examined the results of comparative studies published between 2011 and 2020 to summarize the effects of this instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…According to our results, students were more active and cooperative with the fipped classroom method. Our results were found to be consistent with those of other studies [24][25][26].…”
Section: Discussionsupporting
confidence: 94%
“…According to our results, students were more active and cooperative with the fipped classroom method. Our results were found to be consistent with those of other studies [24][25][26].…”
Section: Discussionsupporting
confidence: 94%
“…However, it remains unclear whether only videos qualify for pre-class materials. As Bond (2020) and Lo and Hew (2021) claim, there is still debate over what constitutes a flipped classroom. However, the essence of the pedagogy is learners’ preparation before class and the subsequent group learning space for interactive-based activities during the class.…”
Section: The Definition Of Flipped Classroomsmentioning
confidence: 99%
“…Due to this, they may have refrained from It is claimed that interaction is one of the crucial factors in flipped learning (Bishop & Verleger, 2013). As such, flipped learning is supposed to be student-centered, giving studentstudent interaction is of paramount importance (Gündüz & Akkoyunlu, 2019;Lo & Hew, 2021;Touchton, 2015;Xiao et al, 2018). However, this study found freshmen's student-student interaction to be the lowest of all factors.…”
Section: Discussionmentioning
confidence: 65%